Deiksis Persona pada Novel Rindu yang Baik untuk Kisah yang Pelik Karya Boy Candra dan Implementasi dalam Pembelajaran Bahasa Indonesia di SMA - Kuntoro Kuntoro; Intan Surya Pratiwi (Journal on Education, 2023)
This study entitled Persona Deixis in the Novel "Rindu yang Baik untuk Kisah yang Pelik" by Boy Candra and its Implementation in Indonesian Language Learning in High School aims to describe (1) the form of persona deixis in the form of the novel "Rindu yang Baik untuk Kisah yang Pelik" by Boy Chandra; (2) the meaning of persona deixis in the novel "Rindu yang Baik untuk Kisah yang Pelik" by Boy Candra; (3) implementation of learning Indonesian in high school. This type of research is a qualitative descriptive research. The data in this study is the text of the novel "Rindu yang Baik untuk Kisah yang Pelik" which contains deixis. While the source of data in this study is the novel "Rindu yang Baik untuk Kisah yang Pelik" by Boy Candra. Data collection techniques use document studies by analyzing persona deixis. Persona deixis in the novel “Rindu yang Baik untuk Kisah yang Pelik” found the use of persona deixis totaling 145 data. Includes 44 data of first person singular persona, 16 data of plural first person deixis, 81 data of second person singular persona, 2 data of plural second person deixis, and 2 data of third person singular deixis.